Artificial SEI membrane modified amorphous carbon material and preparation method and application thereof
By forming an artificial SEI film on the surface of amorphous carbon, the problem of poor transport capacity of amorphous carbon materials in sodium-ion batteries was solved, improving the battery's capacity, efficiency, and stability, and enhancing electrode reaction kinetics.
Patent Information
- Application Number
- CN202411389633.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In sodium-ion batteries, amorphous carbon materials suffer from poor sodium ion transport capacity due to the inhomogeneity and easy solubility of the natural SEI film, which affects the battery's capacity, initial coulombic efficiency, and rate performance.
By forming an artificial SEI film on the surface of amorphous carbon, and using polymerizable monomers and alkali metal compounds to perform in-situ polymerization after heat treatment, a dense SEI film is formed, which improves sodium ion transport and protects amorphous carbon materials, and reduces electrolyte decomposition.
It improves the capacity, initial coulombic efficiency, and rate performance of sodium-ion batteries, enhances electrode reaction kinetics, reduces electrolyte decomposition and the formation of natural SEI films, and improves the cycle stability of the battery.
Smart Images

Figure CN119275289A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of electrode material interface modification methods and material preparation, and specifically relates to an amorphous carbon material modified with an artificial SEI film, and a preparation method and application thereof. Background Art
[0002] As an important member of the energy storage field, the development of negative electrode materials for sodium-ion batteries is very necessary. Current negative electrode materials include amorphous carbon, alloy compounds, etc. Among them, amorphous carbon has low cost and is most likely to be commercialized, but its poor capacity and reaction kinetics limit the development of amorphous carbon. When amorphous carbon is used as a negative electrode active material in sodium-ion batteries, a solid electrolyte interface film (SEI film) will be formed on its surface. The thickness and composition of the SEI film will significantly affect the transmission capacity of sodium ions at the interface, thereby affecting the first coulombic efficiency and rate performance of the sodium-ion battery. The naturally formed SEI film formed by the decomposition of the electrolyte will continue to dissolve during the cycle, affecting the cycle stability. Therefore, improving the interfacial sodium ion transmission capacity of amorphous carbon materials has become an urgent need. Summary of the invention
[0003] Based on the above problems, the present application provides an amorphous carbon material modified with an artificial SEI film, and a preparation method and application thereof. After pre-modification with an artificial SEI film, the decomposition of the electrolyte is reduced and the sodium ion conductivity of the amorphous carbon material is improved, thereby improving the capacity, first coulombic efficiency and rate performance of the sodium ion battery.
[0004] In the first aspect, the present application provides a method for preparing an amorphous carbon material modified with an artificial SEI film, comprising the following steps: step S1, adding amorphous carbon to a nitric acid solution for heat treatment, and then collecting the solid by solid-liquid separation to obtain heat-treated amorphous carbon; the molar concentration of nitric acid in the nitric acid solution is 3.1 mol / L~3.9 mol / L; the heat treatment temperature is 120°C~190°C, and the time is 1.1h~3.0h; step S2, mixing the heat-treated amorphous carbon with water to obtain a suspension, and then adding a polymerization monomer and an alkali metal compound to the suspension for dispersion treatment to obtain a dispersion system; the alkali metal compound includes at least one of an alkali metal salt or an alkali metal oxide; step S3, heating the dispersion system and then performing a heat preservation treatment to allow the polymerization monomer to undergo a polymerization reaction, and then performing solid-liquid separation to collect the solid to obtain an amorphous carbon material modified with an artificial SEI film. The present application firstly heat-treats amorphous carbon with a nitric acid solution, and changes the structure of amorphous carbon by controlling the heat treatment conditions, which is beneficial to improve the interfacial bonding effect between amorphous carbon and polymerized monomers, and then polymerizes the polymerized monomers in situ on the surface of the heat-treated amorphous carbon, and fixes the alkali metal compound in the polymer film layer, and forms an artificial SEI film including polymers and alkali metal compounds on the surface of the heat-treated amorphous carbon. The artificial SEI film can produce a strong adsorption effect with the sodium ions in the electrolyte, reduce the coordination ability of the sodium ions with the solvent molecules, improve the solvation structure, promote ion transport at the solid-liquid interface and enhance the electrode reaction kinetics, thereby improving the rate performance of the sodium ion battery. In addition, the artificial SEI film also protects the amorphous carbon. After being assembled into a sodium ion battery, it can reduce the decomposition of the electrolyte and the formation of the natural SEI film, thereby improving the capacity and first coulomb efficiency of the sodium ion battery.
[0005] In some embodiments, the amorphous carbon includes at least one of soft carbon, hard carbon or graphitized carbon; the particle size of the amorphous carbon is 0.5 μm to 10.0 μm, preferably 2 μm to 8 μm. For example, the particle size of the amorphous carbon is 0.5 μm, 1.0 μm, 1.8 μm, 2.0 μm, 2.4 μm, 3.2 μm, 3.9 μm, 4.4 μm, 5.1 μm, 6.1 μm, 7.0 μm, 7.7 μm, 8.0 μm, 9.2 μm, 9.3 μm, 10.0 μm or a value within the range consisting of any two of them. The present application limits the particle size of amorphous carbon and thereby regulates its specific surface area and surface energy. After heat treatment, the polymerized monomers can be uniformly attached to the surface of the heat-treated amorphous carbon, thereby improving the uniformity of the coating of the artificial SEI film. It is also beneficial to regulate the ratio of amorphous carbon and polymer, improve the sodium ion conductivity of the artificial SEI film, and improve the capacity, rate performance and first coulombic efficiency of the sodium ion battery.
[0006] In the present application, the particle size can be tested by methods known in the art. For example, the particle size of amorphous carbon can be tested by a Malvern particle size tester (model: Mastersizer 3000). The amorphous carbon sample is dispersed in water. After ultrasonic treatment for 30 minutes, the dispersion sample is added to the Malvern particle size tester to test the particle size distribution of the amorphous carbon, and the Dv50 of the amorphous carbon to be tested is obtained as the particle size of the amorphous carbon.
[0007] In some embodiments, the alkali metal compound comprises an alkali metal compound A and an alkali metal compound B; the alkali metal compound A comprises sodium fluoride (NaF), sodium carbonate (Na 2 CO 3 ), sodium oxide (Na 2 O), lithium fluoride (LiF) or lithium oxide (Li 2 O) at least one; alkali metal compound B includes at least one of sodium dodecyl sulfate, sodium hexametaphosphate, sodium polycarboxylate or sodium polyacrylate. The above-mentioned alkali metal compound A and alkali metal compound B are combined to improve the uniformity of the dispersion of the alkali metal compound in the suspension, thereby improving the uniformity of the artificial SEI film, further improving the sodium ion conductivity of the artificial SEI film, and improving the rate performance, capacity and first coulomb efficiency of the sodium ion battery.
[0008] In some embodiments, the mass ratio of amorphous carbon to alkali metal compound is 1:(0.20-0.48); for example, the mass ratio of amorphous carbon to alkali metal compound is 1:0.20, 1:0.23, 1:0.25, 1:0.28, 1:0.33, 1:0.37, 1:0.39, 1:0.42, 1:0.45, 1:0.48 or a value within the range of any two thereof. When the mass of amorphous carbon and alkali metal compound is regulated to meet the above ratio, the alkali metal compound can better exert the conduction effect of sodium ions on the surface of heat-treated amorphous carbon, which is conducive to the rapid embedding and extraction of sodium ions, and further improves the capacity, rate performance and first coulombic efficiency of sodium ion batteries.
[0009] In some embodiments, the mass ratio of alkali metal compound A to alkali metal compound B is 1:(2-7). For example, the mass ratio of alkali metal compound A to alkali metal compound B is 1:2, 1:2.2, 1:2.5, 1:2.9, 1:3.4, 1:3.8, 1:4.0, 1:4.5, 1:4.8, 1:5.4, 1:5.6, 1:5.9, 1:6.3, 1:6.7, 1:7 or a value within the range of any two thereof. When the mass of alkali metal compound A and alkali metal compound B is regulated to meet the above ratio, the two alkali metal compounds can be better matched, the uniformity of the artificial SEI film can be improved, and the capacity, rate performance and first coulombic efficiency of the sodium ion battery can be further improved.
[0010] In some embodiments, the polymerizable monomers include at least one of acrylic acid, methyl methacrylate, acrylonitrile, ethylene glycol, ethylene oxide, and tetrafluoroethylene. The above-mentioned polymerizable monomers have excellent interfacial bonding effects with heat-treated amorphous carbon, which is conducive to in-situ polymerization on the surface of amorphous carbon, and some polymerizable monomers, such as methyl methacrylate, acrylonitrile, ethylene glycol, ethylene oxide, and tetrafluoroethylene, can also cooperate with alkali metal compounds through polar groups after polymerization to jointly enhance the sodium ion conductivity of the artificial SEI film, thereby improving the capacity, rate performance, and first coulombic efficiency of the sodium ion battery.
[0011] In some embodiments, the mass volume ratio of amorphous carbon to polymerized monomer is 1: (2-4) g / mL. Exemplarily, the mass volume ratio of amorphous carbon to polymerized monomer is 1: 2 g / mL, 1: 2.3 g / mL, 1: 2.4 g / mL, 1: 2.5 g / mL, 1: 2.7 g / mL, 1: 2.8 g / mL, 1: 3.1 g / mL, 1: 3.2 g / mL, 1: 3.3 g / mL, 1: 3.5 g / mL, 1: 3.7 g / mL, 1: 3.8 g / mL, 1: 4 g / mL or a value within the range of any two thereof. The mass of amorphous carbon and polymerized monomer is regulated to conform to the above ratio, and the polymerized monomer is excessive compared to amorphous carbon, which is beneficial to promote the combination of the polymerized monomer with the surface of the heat-treated amorphous carbon, as well as with the alkali metal compound, thereby improving the polymerization effect and the quality of the artificial SEI film, and further improving the capacity, rate performance and first coulombic efficiency of the sodium ion battery.
[0012] In some embodiments, the temperature of the heat preservation treatment is 55°C to 120°C, and the time of the heat preservation treatment is 1.6h to 4.8h. Exemplarily, the temperature of the heat preservation treatment is 55°C, 62°C, 66°C, 73°C, 77°C, 81°C, 87°C, 93°C, 96°C, 104°C, 109°C, 110°C, 116°C, 120°C or a value within the range of any two thereof, and the time of the heat preservation treatment is 1.6h, 1.9h, 2.3h, 2.5h, 2.6h, 2.9h, 3.2h, 3.3h, 3.6h, 4.0h, 4.1h, 4.4h, 4.6h, 4.8h or a value within the range of any two thereof. Heat preservation treatment under the above conditions can promote the full progress of the in-situ polymerization reaction, improve the stability and uniformity of the artificial SEI film, and thus help improve the capacity, rate performance and first coulombic efficiency of the sodium ion battery.
[0013] In some embodiments, the dispersion system further comprises a catalyst; the catalyst comprises at least one of potassium periodate, ammonium persulfate, potassium persulfate, concentrated sulfuric acid or sodium thiosulfate.
[0014] In the second aspect, the present application provides an amorphous carbon material modified by an artificial SEI film, which is obtained according to any of the above-mentioned preparation methods; the amorphous carbon material modified by the artificial SEI film includes a substrate and an artificial SEI film disposed on at least a portion of the surface of the substrate; the substrate includes heat-treated amorphous carbon; the artificial SEI film includes a polymer and an alkali metal compound; the mass ratio of the substrate to the polymer is 1: (0.05-0.95). The amorphous carbon material modified by the artificial SEI film of the present application, by coating the surface of the heat-treated amorphous carbon with an artificial SEI film, uses the polymer and alkali metal compound on the artificial SEI film to play a role in conducting sodium ions, thereby improving the embedding and extraction ability of the amorphous carbon material for sodium ions, improving the electrode reaction kinetics of the sodium ion battery, and thus optimizing the rate performance and capacity of the sodium ion battery. At the same time, the artificial SEI film is used to protect the amorphous carbon material, reduce the side reactions of the negative electrode active material and the electrolyte and the formation of the natural SEI film, thereby reducing the consumption of the electrolyte and the negative electrode active material, and improving the first coulomb efficiency of the sodium ion battery.
[0015] Exemplarily, the mass ratio of the amorphous carbon matrix to the polymer is 1:0.05, 1:0.11, 1:0.17, 1:0.22, 1:0.26, 1:0.36, 1:0.43, 1:0.49, 1:0.53, 1:0.62, 1:0.71, 1:0.75, 1:0.84, 1:0.95 or a value within the range of any two thereof. Controlling the mass ratio of the amorphous carbon matrix to the polymer within the above range can further enhance the diffusion capacity of sodium ions in the amorphous carbon material modified with the artificial SEI film, and enhance the capacity, rate performance and first coulombic efficiency of the sodium ion battery.
[0016] In some embodiments, the thickness of the artificial SEI film is 1 nm to 100 nm. For example, the thickness of the artificial SEI film is 1 nm, 5 nm, 12 nm, 23 nm, 28 nm, 36 nm, 42 nm, 52 nm, 61 nm, 67 nm, 76 nm, 78 nm, 87 nm, 93 nm, 100 nm, or a value within the range of any two thereof. When the thickness of the artificial SEI film is adjusted to meet the above range, the sodium ion conduction function can be better exerted, and the capacity, rate performance and first coulombic efficiency of the sodium ion battery can be further improved.
[0017] The present application does not impose any special restrictions on the test method of the thickness of the artificial SEI film, and the test can be performed using methods known in the art. For example, 20 artificial SEI film-modified amorphous carbon material particles can be randomly selected, and the maximum and minimum thickness values of the SEI film on each artificial SEI film-modified amorphous carbon material particle can be observed and counted using a transmission electron microscope, and the arithmetic mean of the maximum and minimum thickness values is calculated as the thickness of the SEI film in the artificial SEI film-modified amorphous carbon material, and then the arithmetic mean of the SEI film thickness of the 20 artificial SEI film-modified amorphous carbon material particles is calculated, which is recorded as the thickness of the artificial SEI film.
[0018] In a third aspect, the present application provides a sodium ion battery comprising a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, and the negative electrode active material layer comprises an amorphous carbon material modified with an artificial SEI film obtained by any of the above preparation methods or any amorphous carbon material modified with an artificial SEI film.
[0019] In some embodiments, the electrolyte includes ethylene carbonate and dimethyl carbonate; based on the mass of the electrolyte, the mass content of ethylene carbonate is 11.0% to 33.5%, and the mass content of dimethyl carbonate is 12.0% to 41.5%. Exemplarily, based on the mass of the electrolyte, the mass content of ethylene carbonate is 11.0%, 12.0%, 14.3%, 15.9%, 16.2%, 18.5%, 21.3%, 23.0%, 23.6%, 26.0%, 26.7%, 28.3%, 30.9%, 32.0%, 33.5% or a value in the range consisting of any two of them; the mass content of dimethyl carbonate is 12%, 12.9%, 15.1%, 16.6%, 20.6%, 23.1%, 24.6%, 27.8%, 29.4%, 31.0%, 33.6%, 36.0%, 37.9%, 39.8%, 41.5% or a value in the range consisting of any two of them. The combination of ethylene carbonate and dimethyl carbonate meeting the above content can further reduce side reactions and the formation of natural SEI film, improve the initial coulombic efficiency and capacity of the sodium ion battery, and also help promote the transmission of sodium ions and improve the rate performance of the sodium ion battery.
[0020] The beneficial effects of this application are at least:
[0021] The present application provides a method for growing an artificial SEI film on an amorphous carbon surface, using a polymerized monomer to undergo a self-polymerization reaction on the amorphous carbon surface to form an artificial SEI film, and at the same time, adding an inorganic component to the precursor solution to achieve the regulation of the SEI film structure. The amorphous carbon material modified by the artificial SEI film obtained by the above method can utilize the mixture of organic materials and inorganic materials in the artificial SEI film to play an ion-conducting role or to play an ion-conducting role after swelling, so that the artificial SEI film and the sodium ions in the electrolyte produce a strong adsorption effect, reduce the coordination ability of sodium ions and solvent molecules, improve the solvation structure, promote ion transport at the solid-liquid interface and enhance the electrode reaction kinetics, thereby improving the capacity and rate performance of the sodium ion battery at high current density. The amorphous carbon material modified by the artificial SEI film can also reduce the reaction decomposition of the electrolyte and the formation of the natural SEI film after being assembled into a sodium ion battery, thereby reducing the capacity loss after the negative electrode active material participates in the reaction, and improving the capacity and first coulomb efficiency of the sodium ion battery. In addition, compared with the natural SEI membrane, the above-mentioned artificial SEI membrane is denser and more stable, and is not easily dissolved in the electrolyte, which makes the sodium-ion battery have better cycle stability.
[0022] Other advantages, objectives and features of the present application will be described in the following description to some extent, and will be apparent to those skilled in the art based on the following examination and study, or can be taught from the practice of the present application to some extent. The objectives and other advantages of the present application can be achieved and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to make the purpose, technical solution and advantages of the present application clearer, the present application will be described in detail below in conjunction with the accompanying drawings, wherein:
[0024] Figure 1 XRD comparison diagram of the hard carbon material modified with the artificial SEI film prepared in Example 1 and the hard carbon material treated by the preparation method of Comparative Example 1;
[0025] Figure 2 This is a Raman comparison diagram of the hard carbon material modified with the artificial SEI film prepared in Example 1 and the hard carbon material treated by the preparation method of Comparative Example 1;
[0026] Figure 3 TEM comparison diagram of the hard carbon material modified with the artificial SEI film prepared in Example 2 and the hard carbon material treated by the preparation method of Comparative Example 2;
[0027] Figure 4 A comparison chart of the rate performance of the hard carbon material modified with the artificial SEI film prepared in Example 2 and the hard carbon material treated by the preparation method of Comparative Example 2;
[0028] Figure 5 This is a comparison chart of the charge and discharge curves of the hard carbon material modified with the artificial SEI film prepared in Example 3 and the hard carbon material treated by the preparation method of Comparative Example 3. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0030] In the process of studying amorphous carbon materials, the inventors found that the natural SEI film is thick and uneven, which will significantly affect the interfacial transport of sodium ions. When an artificial SEI film is used to coat amorphous carbon materials, since the artificial SEI film is more commonly used in alkali metal batteries and lithium-ion batteries, such as lithium metal negative electrodes, sodium metal negative electrodes, and graphite negative electrodes. For amorphous carbon negative electrodes of sodium ion batteries, the synthesis and coating of artificial SEI are very difficult and difficult to achieve. Therefore, the present application provides a method for effectively synthesizing an artificial SEI film on the surface of amorphous carbon.
[0031] In the first aspect, the method for preparing an artificial SEI film-modified amorphous carbon material provided in the present application may specifically include the following steps: step S1, step S1, adding amorphous carbon to a nitric acid solution for heat treatment, and then collecting the solid by solid-liquid separation to obtain heat-treated amorphous carbon; the molar concentration of nitric acid in the nitric acid solution is 3.1 mol / L to 3.9 mol / L; the heat treatment temperature is 120°C to 190°C, and the time is 1.1h to 3.0h.
[0032] Step S2, mixing the heat-treated amorphous carbon with water to obtain a suspension, and then adding a polymerized monomer and an alkali metal compound to the suspension for dispersion treatment to obtain a dispersion system; the alkali metal compound includes at least one of an alkali metal salt or an alkali metal oxide. Specifically, it can include uniformly dispersing the heat-treated amorphous carbon in water to form a dispersion A, where the dispersion A is a suspension. Subsequently, the molecular-level polymerized monomer is used as a SEI precursor, and the alkali metal compound is uniformly dispersed in water to form a dispersion B, and then the dispersion A and the dispersion B are uniformly mixed to obtain a dispersion system.
[0033] Step S3, heating the dispersed system and then performing heat preservation treatment to make the polymerized monomer undergo polymerization reaction, the SEI precursor will undergo self-polymerization and wrap around the surface of the heat-treated amorphous carbon, and the alkali metal compound will also be distributed inside the polymer. Then, the solid particles are collected by solid-liquid separation to obtain an amorphous carbon material modified with an artificial SEI film, and the solid particles are collected and dried to obtain an amorphous carbon material modified with an artificial SEI film.
[0034] The present application uses a self-polymerization method to self-polymerize organic and inorganic molecules on the surface of heat-treated amorphous carbon, so that an artificial SEI film that conducts sodium ions is coated on the surface of the amorphous carbon, thereby reducing the decomposition of the electrolyte and the formation of the natural SEI film after being assembled into a sodium ion battery, thereby improving the first coulomb efficiency. At the same time, the artificial SEI film of the present application is denser and more stable than the natural SEI film, and is not easy to dissolve in the electrolyte, thus having better cycle stability. In addition, the artificial SEI film of the present application is thinner and has better ionic conductivity, so that sodium ions can pass through the interface faster and obtain better reaction kinetics.
[0035] The above-mentioned heat preservation treatment method also includes allowing the polymerization monomer to self-polymerize under conditions such as adding a catalyst, irradiating light and / or ultraviolet radiation, etc.
[0036] In some embodiments, amorphous carbon is soft carbon, hard carbon, or graphitized carbon sintered from a carbon source precursor at high temperature, and the carbon source precursor includes asphalt, petroleum coke, coal, coconut shell, walnut shell, corn stalk, glucose, sucrose, starch, etc. Preferably, amorphous carbon is hard carbon.
[0037] In some embodiments, the polymerizable monomers include various organic macromolecules that can undergo polymerization reactions and conduct ions after polymerization, or swell with the electrolyte after polymerization to conduct ions, such as at least one of methyl methacrylate, ethylene glycol, ethylene oxide, acrylic acid, tetrafluoroethylene, acrylonitrile and the like.
[0038] In some embodiments, the dispersion method includes stirring, ultrasound, adding a dispersant, and the like.
[0039] In the second aspect, the present application provides an amorphous carbon material modified with an artificial SEI film, which is obtained according to any of the above-mentioned preparation methods; the amorphous carbon material modified with an artificial SEI film includes a substrate and an artificial SEI film coated on at least a portion of the surface of the substrate; the substrate includes heat-treated amorphous carbon; the artificial SEI film includes a polymer and an alkali metal compound; the mass ratio of the amorphous carbon substrate and the polymer is 1:(0.05~0.95).
[0040] In a third aspect, the present application provides a sodium ion battery comprising a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, and the negative electrode active material layer comprises an amorphous carbon material modified with an artificial SEI film obtained by any of the above preparation methods or any amorphous carbon material modified with an artificial SEI film.
[0041] In some embodiments, the negative electrode current collector includes at least one of aluminum foil, copper foil or stainless steel foil. In the present application, the negative electrode active material layer also includes a binder, and the binder includes at least one of sodium cellulose, sodium carboxymethyl cellulose, hydroxypropyl cellulose, sodium hydroxymethyl cellulose, potassium hydroxymethyl cellulose, diacetyl cellulose, polyacrylic acid, sodium alginate, styrene-butadiene rubber, acrylic butadiene rubber, polypyrrole, polyaniline, epoxy resin or guardo gum.
[0042] In some embodiments, the preparation method of the above-mentioned negative electrode plate includes the following steps: adding the above-mentioned artificial SEI film-modified amorphous carbon material and polymer binder to a solvent and stirring them into a uniform slurry, coating the slurry on the negative electrode collector, and drying to obtain the negative electrode; wherein the solvent can be selected from at least one of water, acetone, N-methylpyrrolidone, dimethylformamide or ethanol.
[0043] In the present application, the sodium ion battery also includes a positive electrode, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material may include at least one of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries can also be used.
[0044] In some embodiments, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr or Ce. The sodium transition metal oxide is, for example, Na x MO 2 , wherein M is at least one of Ti, V, Mn, Co, Ni, Fe, Cr or Cu, and 0<x≤1.
[0045] In some embodiments, the polyanionic compound may be a compound having sodium ions, transition metal ions and tetrahedral (YO 4 ) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr or Ce; Y can be at least one of P, S or Si; n represents (YO 4 ) n- valence state.
[0046] The polyanionic compound can also be a compound having sodium ions, transition metal ions, tetrahedral (YO 4 ) n-A class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr or Ce; Y can be at least one of P, S or Si, and n represents (YO 4 ) n- valence state; the halogen may be at least one of F, Cl or Br.
[0047] The polyanionic compound can also be a compound having sodium ions, tetrahedral (YO 4 ) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S or Si, and n represents (YO 4 ) n- valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr or Ce; m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl or Br.
[0048] Polyanionic compounds are, for example, NaFePO 4 、Na 3 V 2 (PO 4 ) 3 、NaM'PO 4 F (M' is one or more of V, Fe, Mn and Ni) or Na 3 (VO y ) 2 (PO 4 ) 2 F 3-2y At least one of (0≤y≤1).
[0049] Prussian blue compounds can be sodium ions, transition metal ions and cyanide ions (CN - ). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN) 6 , wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co or Zn, 0<a≤2, 0<b<1, 0<c<1.
[0050] In some embodiments, the positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The present application does not specifically limit the type of the conductive agent, and may be selected according to actual needs. As an example, the conductive agent may be at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, or carbon nanofibers.
[0051] In some embodiments, the positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and the optional conductive agent to the positive electrode current collector. The present application does not specifically limit the type of binder, and it can be selected according to actual needs. As an example, the binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA) or carboxymethyl chitosan (CMCS).
[0052] In some embodiments, the positive electrode current collector may be a conductive carbon sheet, a metal foil, a carbon-coated metal foil, a porous metal plate or a composite current collector, wherein the conductive carbon material of the conductive carbon sheet may be at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene or carbon nanofibers, and the metal material of the metal foil, the carbon-coated metal foil and the porous metal plate may be independently selected from at least one of copper, aluminum, nickel or stainless steel. The composite current collector may be a composite current collector formed by a metal foil and a polymer base film.
[0053] The positive electrode current collector is, for example, one or more of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh and carbon-coated aluminum foil, preferably aluminum foil.
[0054] The positive electrode can be prepared according to conventional methods in the art. Usually, the positive electrode active material and optional conductive agent and binder are dispersed in a solvent (such as N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry, which is then coated on the positive electrode current collector, and then dried and cold pressed to obtain the positive electrode.
[0055] The sodium ion battery of the present application also includes an isolation membrane, which can be any material suitable for an isolation membrane of an electrochemical energy storage device in the art, for example, it can be at least one of but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester or natural fiber.
[0056] The electrolyte may include an organic solvent and an electrolyte sodium salt. As an example, the organic solvent may also include at least one of propylene carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, or methyl tert-butyl ether; the electrolyte sodium salt may be at least one of sodium hexafluorophosphate, sodium bis(trifluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, or sodium chloride.
[0057] The positive electrode, the separator, and the negative electrode are stacked in order, so that the separator is between the positive electrode and the negative electrode to play an isolating role, to obtain a battery cell, or the battery cell can be obtained after winding; the battery cell is placed in a packaging shell (which can be a soft package, a square aluminum shell, a square steel shell, a cylindrical aluminum shell and a cylindrical steel shell), an electrolyte is injected and sealed to obtain a sodium ion battery.
[0058] The following describes the implementation methods of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present application in a schematic manner, and the following embodiments and the features in the embodiments can be combined with each other without conflict.
[0059] Unless otherwise specified, the raw materials used in the following examples are all from common commercially available products, and the devices or equipment used are all purchased from conventional market sales channels.
[0060] Example 1
[0061] A method for preparing an artificial SEI film-modified amorphous carbon material comprises the following steps:
[0062] Step S1: Take KURANODE type 1 hard carbon as raw material, and use 1g of hard carbon material as amorphous carbon, and place it in a planetary ball mill for crushing to a particle size of 5.5μm. Place the hard carbon powder obtained by ball milling in a 3.5mol / L nitric acid solution and stir for 30min, then heat treat it at 160℃ for 1.5h, and take out the heat-treated amorphous carbon after it cools down to room temperature naturally.
[0063] Step S2, use 1000mL of deionized water to filter and wash the above-mentioned heat-treated amorphous carbon three times, and then disperse it in water to obtain a suspension of hard carbon powder. To the above suspension, add 3mL of 99% purity acrylic acid monomer until it is completely dissolved, add 50mg of sodium fluoride, and then add 200mg of potassium periodate as a catalyst, and then add 200mg of sodium dodecyl sulfate. The mass ratio of hard carbon and alkali metal compound is 1:0.25, and the mass ratio of sodium fluoride and sodium dodecyl sulfate is 1:4. Then place the obtained solid-liquid mixture in a centrifuge and centrifuge it at a speed of 8000rpm for 12min to obtain a dispersed system.
[0064] Step S3, placing the dispersed system in a beaker, heating to 100°C, keeping the temperature for 3 hours, and stirring vigorously to polymerize the acrylic acid to form polyacrylic acid on the hard carbon surface. Then, the solid is collected by solid-liquid separation, washed with 1000 mL of deionized water and ethanol for 3 times, and dried in a 60°C forced air drying oven for 12 hours to obtain a hard carbon material modified with an artificial SEI film, that is, an amorphous carbon material modified with an artificial SEI film.
[0065] The artificial SEI film modified hard carbon material obtained in Example 1 includes a hard carbon substrate and an artificial SEI film arranged on the surface of the hard carbon substrate, wherein the artificial SEI film includes polyacrylic acid, sodium fluoride and sodium dodecyl sulfate; the mass ratio of the substrate to the polymer is 1:0.25. The thickness of the artificial SEI film is 11 nm.
[0066] In the preparation method of Comparative Example 1, the hard carbon is treated in the same steps as in Example 1, except that no acrylic acid monomer is added in step S2.
[0067] Performance Testing
[0068] Figure 1 The XRD comparison diagram of the hard carbon material modified with the artificial SEI film prepared in Example 1 and the hard carbon material treated by the preparation method of Comparative Example 1, wherein HC is the hard carbon material treated by the preparation method of Comparative Example 1, and AS-HC is the hard carbon material modified with the artificial SEI film prepared in Example 1. Figure 1 It can be seen that after artificial SEI modification, the characteristic peak of hard carbon has no obvious change. Figure 2 The Raman comparison diagram of the hard carbon material modified with the artificial SEI film prepared in Example 1 and the hard carbon material treated by the preparation method of Comparative Example 1, wherein a is the hard carbon material treated by the preparation method of Comparative Example 1, and b is the hard carbon material modified with the artificial SEI film prepared in Example 1. Figure 2 It can be seen that the ID / IG value of the hard carbon material modified by the artificial SEI film prepared in Example 1 is slightly increased, indicating that the introduction of the artificial SEI film hardly changes the bulk structure of the hard carbon.
[0069] Preparation method of sodium ion battery:
[0070] (1) The artificial SEI film modified hard carbon material prepared in Example 1 and the hard carbon material treated by the preparation method of Comparative Example 1 were mixed and ground with sodium alginate at a mass ratio of 9:1, and deionized water was added for wet grinding until the slurry could pass through a 200-mesh stainless steel sieve;
[0071] (2) using a wet film applicator, the two slurries ground in step (1) were respectively coated on the copper foil to a thickness of 200 μm, and then transferred to a vacuum oven at 120° C. and dried for 12 h;
[0072] (3) The two electrodes described in step (2) were cut into small discs with a diameter of 12 mm and transferred to a glove box filled with argon. The button cells were assembled in the order of negative electrode shell, spring, gasket, sodium metal sheet, diaphragm, small disc electrode, and positive electrode shell, and 150 μL of electrolyte was added (the button cell model used was CR2032, the diaphragm was a glass fiber diaphragm, and the electrolyte was sodium hexafluorophosphate (NaPF 6 ) is dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate (mass ratio is 1:1), wherein, based on the mass of the electrolyte, NaPF 6 The mass percentage is 12%).
[0073] (4) After assembly, the two button cells were removed from the glove box and left to stand at room temperature for 8 h before being subjected to an electrochemical performance test on a LAND battery testing system.
[0074] First coulombic efficiency test: discharge the sodium ion battery at a constant current of 0.1C to a cut-off voltage of 0V, and measure the discharge specific capacity of the sodium ion battery; charge the sodium ion battery at a constant current of 0.1C to a cut-off voltage of 2.5V, and measure the charge specific capacity of the sodium ion battery. First coulombic efficiency = charge specific capacity / discharge specific capacity × 100%.
[0075] The test shows that the discharge capacity of the artificial SEI film modified hard carbon material prepared in Example 1 is 427 mAh·g -1 , the charging capacity is 350mAh g -1 The first coulombic efficiency is 82%; the discharge specific capacity of the hard carbon material treated by the preparation method of comparative example 1 is 443 mAh·g -1 , the charging capacity is 341mAh g -1 , the first coulombic efficiency is 77%. It can be seen that after modification by the artificial SEI film, the first coulombic efficiency of the hard carbon material modified by the artificial SEI film has increased significantly.
[0076] Example 2
[0077] A method for preparing an artificial SEI film-modified amorphous carbon material specifically comprises the following steps:
[0078] Step S1: Take coconut shell-based hard carbon as raw material, take 1g of hard carbon material as amorphous carbon, and place it in a planetary ball mill for crushing to a particle size of 5.5μm. Place the hard carbon powder obtained by ball milling in a 3.5mol / L nitric acid solution and stir for 30min, then heat treat it at a temperature of 160°C for 1.5h, and take out the heat-treated amorphous carbon after it is naturally cooled to room temperature.
[0079] Step S2, the heat-treated amorphous carbon was filtered and washed three times with 1000 mL of deionized water, and then dispersed in water to obtain a suspension of hard carbon powder. To the suspension, 3 mL of methyl methacrylate monomer with a purity of 99% was added, followed by 200 mg of sodium dodecyl sulfate and 150 mg of ammonium persulfate powder, and the mass ratio of hard carbon to alkali metal compound was 1:0.2. The obtained solid-liquid mixture was then placed in a centrifuge and centrifuged at 8000 rpm for 12 minutes to obtain a dispersed system.
[0080] Step S3, placing the dispersed system in a beaker, heating to 70°C, keeping the temperature for 3 hours, and stirring vigorously to polymerize the methyl methacrylate solution to form polymethyl methacrylate on the hard carbon surface. Then, the solid is collected by solid-liquid separation, washed with 1000 mL of deionized water and ethanol for 3 times, and dried in a 60°C forced air drying oven for 12 hours to obtain a hard carbon material modified with an artificial SEI film, that is, an amorphous carbon material modified with an artificial SEI film.
[0081] The artificial SEI film modified hard carbon material obtained in Example 2 includes a hard carbon substrate and an artificial SEI film arranged on the surface of the hard carbon substrate, wherein the artificial SEI film includes polymethyl methacrylate and sodium dodecyl sulfate; the mass ratio of the substrate to the polymer is 1:0.24. The thickness of the artificial SEI film is 10 nm.
[0082] In the preparation method of Comparative Example 2, the hard carbon is treated in the same steps as in Example 1, except that no methyl methacrylate monomer is added in step S2.
[0083] Performance Testing
[0084] Figure 3TEM comparison diagram of the hard carbon material modified with an artificial SEI film prepared in Example 2 and the hard carbon material treated by the preparation method of Comparative Example 2, wherein a is the hard carbon material treated by the preparation method of Comparative Example 2, and b is the hard carbon material modified with an artificial SEI film prepared in Example 2. It can be seen from TEM that the hard carbon material modified with an artificial SEI film prepared in Example 2 includes a hard carbon substrate and an artificial SEI film disposed on the surface of the hard carbon substrate, and the thickness of the artificial SEI film is 10 nm.
[0085] According to the aforementioned method for preparing a sodium ion battery, a sodium ion battery was prepared by using the artificial SEI film-modified hard carbon material prepared in Example 2 and the hard carbon material treated by the preparation method of Comparative Example 2, and then a rate performance test was performed. Figure 4 The figure is a comparison chart of the rate performance of the hard carbon material modified by the artificial SEI film prepared in Example 2 and the hard carbon material treated by the preparation method of Comparative Example 2, wherein HC is the hard carbon material treated by the preparation method of Comparative Example 2, and AS-HC is the hard carbon material modified by the artificial SEI film prepared in Example 2. The rate performance test includes: Figure 4 The constant current charge and discharge were performed according to the number of cycles and current density, the current density was selected from 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 0.1C (1C = 300mA / g), the constant current discharge cut-off voltage was 0V, the constant current charge cut-off voltage was 2.5V, and each current density was cycled 5 times to test the capacity of the hard carbon material modified by the artificial SEI film of the embodiment and the hard carbon material treated in the comparative example. Figure 4 It can be seen that after modification with the artificial SEI film, at a high current density of 1C to 5C, after the same number of cycles, the capacity of Example 2 is significantly improved, showing a more excellent rate performance.
[0086] Example 3
[0087] A method for preparing an artificial SEI film-modified amorphous carbon material specifically comprises the following steps:
[0088] Step S1: Take phenolic resin hard carbon as raw material, take 1g of hard carbon material as amorphous carbon, and place it in a planetary ball mill for crushing to a particle size of 5.5μm. Place the hard carbon powder obtained by ball milling in a 3.5mol / L nitric acid solution and stir for 30min, then heat treat it at a temperature of 160℃ for 1.5h, and take out the heat-treated amorphous carbon after it cools down to room temperature naturally.
[0089] Step S2, filter and wash the above-mentioned heat-treated amorphous carbon three times with 1000mL of deionized water, and then disperse it in water to obtain a suspension of hard carbon powder. Slowly add acrylonitrile monomer to the above suspension until the mass volume ratio of hard carbon and acrylonitrile is 1:3g / mL. Add 50mg of sodium carbonate, followed by 20 drops of concentrated sulfuric acid, 25mL of 2% potassium persulfate solution, and 5mL of 10% sodium thiosulfate solution, and then add 200mg of sodium dodecyl sulfate. The mass ratio of hard carbon and alkali metal compounds is 1:0.25, and the mass ratio of sodium carbonate and sodium dodecyl sulfate is 1:4. Then place the obtained solid-liquid mixture in a centrifuge and centrifuge it at 8000rpm for 12min to obtain a dispersed system.
[0090] Step S3, placing the dispersed system in a beaker, heating to 60°C, keeping the temperature for 3 hours, and stirring vigorously to polymerize acrylonitrile to form polyacrylonitrile on the hard carbon surface. Then, the solid is collected by solid-liquid separation, washed with 1000 mL of deionized water and ethanol for 3 times, and dried in a 60°C forced air drying oven for 12 hours to obtain a hard carbon material modified with an artificial SEI film, that is, an amorphous carbon material modified with an artificial SEI film.
[0091] The artificial SEI film modified hard carbon material obtained in Example 3 includes a hard carbon substrate and an artificial SEI film arranged on the surface of the hard carbon substrate, wherein the artificial SEI film includes polyacrylonitrile, sodium carbonate and sodium dodecyl sulfate; the mass ratio of the substrate to the polymer is 1:0.31. The thickness of the artificial SEI film is 13 nm.
[0092] In the preparation method of Comparative Example 3, the hard carbon is treated in the same steps as in Example 3, except that no acrylonitrile monomer is added in step S2.
[0093] In the preparation method of Example 4, hard carbon is treated by the same steps as in Example 3, with the only difference being that an equal mass of sodium carbonate is used instead of sodium dodecyl sulfate in step S2.
[0094] The preparation method of Comparative Example 4 is different from that of Example 3 only in that the heat treatment step of step S1 is omitted, hard carbon is used instead of heat-treated amorphous carbon, and the operations of steps S2 and S3 are directly performed.
[0095] Performance Testing
[0096] According to the aforementioned method for preparing a sodium ion battery, a sodium ion battery was prepared from the artificial SEI film-modified hard carbon material prepared in Example 3 and Example 4, and the hard carbon material treated by the preparation method of Comparative Example 3 and Comparative Example 4, and then the charge and discharge performance was tested. Figure 5The charge and discharge curves of the artificial SEI film modified hard carbon material prepared in Example 3 and the hard carbon material treated by the preparation method of Comparative Example 3 are compared, wherein a is the artificial SEI film modified hard carbon material prepared in Example 3, and b is the hard carbon material treated by the preparation method of Comparative Example 3. The charge and discharge method is: constant current discharge with a current of 0.1C and a cut-off voltage of 0V, and then constant current charging with a current of 0.1C and a cut-off voltage of 2.5V. Figure 5 It can be seen that the capacity (in terms of charging capacity) of the artificial SEI film modified hard carbon material prepared in Example 3 is 430 mAh·g -1 The capacity (in terms of charging capacity) of the hard carbon material treated by the preparation method of Comparative Example 3 is 375 mAh·g -1 It can be seen that after modification by the artificial SEI film, the capacity of the hard carbon material modified by the artificial SEI film has increased significantly. The reason for the increase in capacity of Example 3 at a current density of 0.1C may be that: Example 3 uses a variety of alkali metal compounds, and the coordination of polymers and alkali metal compounds on the SEI film can promote reaction kinetics and further improve the conduction effect on sodium ions, thereby increasing the capacity at 0.1C.
[0097] The artificial SEI film modified hard carbon material prepared in Example 4 was subjected to the above constant current charge and discharge test, specifically, constant current discharge was performed at a current of 0.1C, the cut-off voltage was 0V, and then constant current charging was performed at a current of 0.1C, the cut-off voltage was 2.5V, and the capacity (in terms of charging capacity) of the artificial SEI film modified hard carbon material prepared in Example 4 was 395 mAh·g -1 Compared with Example 3, it can be seen that the present application can further improve the capacity of the sodium ion battery by combining the alkali metal compound A and the alkali metal compound B.
[0098] The hard carbon material treated by the preparation method of comparative example 4 was subjected to the above constant current charge and discharge test, specifically, the constant current discharge was performed at a current of 0.1C, the cut-off voltage was 0V, and then the constant current charge was performed at a current of 0.1C, the cut-off voltage was 2.5V, and the capacity (in terms of charging capacity) of the hard carbon material treated by the preparation method of comparative example 4 was 403 mAh·g -1 Compared with Example 3, it can be seen that the present application changes the structure of amorphous carbon through a heat treatment process, which is beneficial to improving the capacity of the sodium ion battery.
[0099] In summary, the present application discloses an amorphous carbon material modified with an artificial SEI film and a preparation method thereof, wherein the thickness of the artificial SEI film is 1nm to 100nm, which can effectively conduct sodium ions, improve reaction kinetics, and significantly increase rate performance after being assembled into a sodium ion battery. At the same time, due to the presence of the artificial SEI film, the decomposition of the electrolyte and the formation of the natural SEI film can be reduced, and its capacity and first coulombic efficiency can also be effectively improved.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the scope of the technical solution, which should be included in the scope of the claims of the present application.
Claims
1. A method for preparing an artificial SEI film-modified amorphous carbon material, characterized in that: The following steps are involved: Step S1, adding amorphous carbon to a nitric acid solution for heat treatment, and then collecting solids by solid-liquid separation to obtain heat-treated amorphous carbon; the molar concentration of nitric acid in the nitric acid solution is 3.1 mol / L to 3.9 mol / L; the temperature of the heat treatment is 120° C. to 190° C., and the time is 1.1 h to 3.0 h; Step S2, mixing the heat-treated amorphous carbon with water to obtain a suspension, and then adding a polymerizable monomer and an alkali metal compound to the suspension for dispersion treatment to obtain a dispersion system; the alkali metal compound includes at least one of an alkali metal salt or an alkali metal oxide; Step S3, heating the dispersed system and then performing heat preservation treatment to allow the polymerization monomer to undergo a polymerization reaction, and then collecting the solid by solid-liquid separation to obtain the artificial SEI film-modified amorphous carbon material.
2. The preparation method according to claim 1, characterized in that: The amorphous carbon includes at least one of soft carbon, hard carbon or graphitized carbon; the particle size of the amorphous carbon is 0.5 μm to 10.0 μm, preferably 2 μm to 8 μm.
3. The preparation method according to claim 1 or 2, characterized in that: The alkali metal compound comprises an alkali metal compound A and an alkali metal compound B; The alkali metal compound A includes at least one of sodium fluoride, sodium carbonate, sodium oxide, lithium fluoride or lithium oxide; the alkali metal compound B includes at least one of sodium dodecyl sulfate, sodium hexametaphosphate, sodium polycarboxylate or sodium polyacrylate.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the amorphous carbon to the alkali metal compound is 1:(0.20-0.48); and / or, The mass ratio of the alkali metal compound A to the alkali metal compound B is 1:(2-7).
5. The preparation method according to claim 1 or 2, characterized in that: The polymerizable monomer comprises at least one of acrylic acid, methyl methacrylate, acrylonitrile, ethylene glycol, ethylene oxide, and tetrafluoroethylene; the mass volume ratio of the amorphous carbon to the polymerizable monomer is 1: (2-4) g / mL.
6. The preparation method according to claim 1 or 2, characterized in that: The temperature of the heat preservation treatment is 55° C. to 120° C., and the time of the heat preservation treatment is 1.6 h to 4.8 h; and / or, The dispersed system further comprises a catalyst; the catalyst comprises at least one of potassium periodate, ammonium persulfate, potassium persulfate, concentrated sulfuric acid or sodium thiosulfate.
7. An amorphous carbon material modified by an artificial SEI film, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 6; The artificial SEI film-modified amorphous carbon material comprises a substrate and an artificial SEI film disposed on at least a portion of the surface of the substrate; the substrate comprises the heat-treated amorphous carbon; The artificial SEI film includes a polymer and the alkali metal compound; The mass ratio of the matrix to the polymer is 1:(0.05-0.95).
8. The artificial SEI film-modified amorphous carbon material according to claim 7, characterized in that: The thickness of the artificial SEI film is 1 nm to 100 nm.
9. A sodium ion battery, characterized in that: The invention comprises a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises an amorphous carbon material modified with an artificial SEI film obtained by the preparation method according to any one of claims 1 to 6 or an amorphous carbon material modified with an artificial SEI film according to claim 7 or 8.
10. The sodium ion battery according to claim 9, characterized in that: The electrolyte comprises ethylene carbonate and dimethyl carbonate; based on the mass of the electrolyte, the mass content of the ethylene carbonate is 11.0% to 33.5%, and the mass content of the dimethyl carbonate is 12.0% to 41.5%.
Citation Information
Patent Citations
Preparation method and application of polymer-modified biomass hard carbon negative electrode material
CN115231545A
Interface modified sodium ion battery hard carbon negative electrode material / negative electrode, preparation method and application
CN117317153A
KR20240103440A